(untitled) (LEARNing Landscapes, 2018)
During the Soviet era, the Kazakh language underwent harsh times and was on the brink of extinction from urban areas in Kazakhstan. Today, the country is paving its way towards reviving the language. This article details an effort to support Kazakh language learning in motivating secondary school students through the use of technology. Through the development of a small-scale project connecting university students as Near Peer Role Models (NPRM) with secondary school students, we used WhatsApp texting group chats as a means to encourage authentic communication in the Kazakh language and discovered five tangible results and suggested next steps.